Pengaruh Ekstrak Buah Labu Siam (Sechium edule) terhadap Ketebalan Dinding Aorta Tikus Putih (Rattus norvegicus strain wistar) Model Aterosklerosis - Desy Andari; Aulia Wiraldi Putra; Meddy Setiawan (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2022)
Background: Atheroslerosis is a disease that formed due to cumulation of the fibrous tissues in vascular wall and gradually become thrombus. Chayote contains antioxidants such flavonoid, saponin, and ascorbic acid that could prevent the thickening of the vascular wall. Objective: To determine the effect of chayote extract on aortic vascular wall thickness in white rats with atherosclerosis model. Methods: True experimental with post-test only controlled group design. Sixteen white male rats divided into 4 groups: positive control group and 3 treatment groups that given chayote extract at different doses (20 mg/day, 40 mg/day, 80 mg/day). The H&E stained aortic preparate were observed with 400x magnification used optical microscope and vascular thickness were measured with optilab software. Data analized with one way ANOVA, post hoc, pearson and linear regression test. Result: There was significant effect of chayote extract to the aortic arch vascular wall thickness (ANOVA p=0,001) and the dose that started giving effect was 40 mg/day (Post Hoc test). There was very strong, significant, and reciprocally correlation between chayote extract and aortic wall thickness (R=-0,896). Chayote extract affected aortic wall thickness with the value of 80,4%. Conclusion: Chayote extract could prevent the thickening of aortic wall in atherosclerotic rats.